Al-Ḥājj ‘Umar Sa‘īd Shukrū Amīnūtū: Ḥayātu wa Kifāhuh wa Afkāruh - Agus Salim Daulay (Studia Islamika, 1997)
HOS Tjokroaminoto, to this day, tends to be considered as a Sarekat Islam (Islam Union) important figure only, whereas he was one of the actors who contributed to the formation of Indonesian modern history.DOI: 10.15408/sdi.v4i4.768